Difference: AVFedotovHowToSolveFFequalsToXsquaredMinus2 (1 vs. 2)

Revision 22012-03-10 - AlexanderFedotov

Line: 1 to 1
 
META TOPICPARENT name="AVFedotovHowTo"
<!--
   ==================
Line: 36 to 36
 
Changed:
<
<
First, let us note that the equation
>
>
Solution:

  • First, it is noteworthy that the equation
 
has simple solutions
Changed:
<
<
One can try to reduce (1) to (2) by changing "coordinates" with
>
>
  • One can try to reduce (1) to (2) by changing "coordinates" with
 
Changed:
<
<
In y coordinates, eq.(1) can be written down as
>
>
  • In y coordinates, eq.(1) can be rewritten as
 
where
Changed:
<
<
Requiring eq.(2) for gives
>
>
  • Requesting eq.(2) to hold for gives
 
or
Changed:
<
<
>
>
 or
where we denoted
Line: 62 to 65
 of the eq.(7)) into a solution of eq.(1):
Added:
>
>
  • Looking for solutions of eq.(9)
    • Assumption 1: is defined in the vicinity of
      • Assumption 2A: and its derivatives of all orders are finite at . Then, by comparing Taylor-series expansions for the left- and right-hand sides of eq.9, one can conclude that all the derivatives are zeros, i.e. . The corresponding solutions, and , are of no interest for us, as these functions are not invertible.
      • A singularity of at is needed.
        • Assumption 2B:
          • Assumption 3: at with
            • A good guess:
              is a solution for any
              • Properties:
                • defined at
                • has maxima at and
                  and one minimum
                  • there are two inverse functions, both defined in the interval , and taking values in the intervals and respectively
              • Independently of the value, all the solutions will give the same result when fed into eq.(11)
                Therefore, we can consider the details for just one case of e.g. :
                • The two inverse functions are
                  or for

  • Feeding the found solution into the formula (11)
    According to (11) we get -- the solution of eq.(1) -- in three steps:
    1. taking : with eq.(13.1), the result is
    2. applying one of two functions to the result of step 1: taking e.g. , gives
    3. finally, applying function (12.1) for the argument resulting from the step 2:

  • Remarks
    • Due to specific properties of the function applied on step 3, the result does not depend on which one out of the two functions is chosen on step 2
    • If the general solution (13) is taken instead of (13,1) on step 1, then an additional exponential power appears on step 1 and gets propagated on step 2. Then, on step 3, the general formula (13) is applied instead of (13.1), and this involves the extra power, which cancels the power. So the result does not change.
    • The results are identical for the plus and minus signs in the formula used on step 1.
      Indeed, , Therefore, changing plus to minus just exchanges the terms and on step 3.
 

Revision 12012-03-10 - AlexanderFedotov

Line: 1 to 1
Added:
>
>
META TOPICPARENT name="AVFedotovHowTo"
<!--
   ==================
   SETTINGS FOR THIS PAGE: (active are only those with 3 spaces before `*')
   ==================
                                HIGHLIGT (VERBATIM and SYNTAX)
 * Set USERSTYLEURL = https://twiki.cern.ch/twiki/pub/Main/AlexanderFedotov/My_Highlight.css

HIDE LEFT BAR * Set USERSTYLEURL = https://twiki.cern.ch/twiki/pub/TWiki/PatternSkinCssCookbookNoLeftBar/hideleftbar.css

HIGHLIGT + HIDE LEFT BAR

LATEX VIA MATHMODEPLUGIN

DEFINE A VARIABLE (reference with %My40Blanks%) * Set My40Blanks =                                         

AN ALTERNATIVE (this works only if defined in More Topic Actions -> Edit topic preference settings ) * Set My40Blanks =

-->

Trying to solve f(f(x)) = x**2 - 2

Problem: Find satisfying the functional equation

First, let us note that the equation

has simple solutions

One can try to reduce (1) to (2) by changing "coordinates" with

In y coordinates, eq.(1) can be written down as
where

Requiring eq.(2) for gives

or
or
where we denoted
Now a solution g(y) of the new functional equation (9) will transform a solution (3) of eq.(2) (more precisely, the solution of the eq.(7)) into a solution of eq.(1):


 
This site is powered by the TWiki collaboration platform Powered by PerlCopyright & 2008-2019 by the contributing authors. All material on this collaboration platform is the property of the contributing authors.
Ideas, requests, problems regarding TWiki? Send feedback